The alternative between carnality and intentionality in the practice of surrogacy - Guazzoni, Marta (Medicina e Morale, 2025)
The purpose of this article is to reflect on a particular implication of the practice of surrogacy: the unprecedented possibility of fragmenting the maternal continuum and multiplying female subjectivities in the generative process, thus leaving in suspension an anthropologically and existentially crucial question: “Who is my mother?” In the attempt to answer this question, the contemporary debate radically splits, defining maternal status from the opposition between carnality and intentionality. The critical analysis of the arguments by which maternal status is assigned in the debate now to the pregnant woman and now to the woman socially charged with caring for the unborn child, will be followed by that of the disturbingly widespread claim today to reread the human person and her experiences under the banner of disembodiment.